2018
DOI: 10.4103/sni.sni_36_18
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular anastomosis under 3D exoscope or endoscope magnification: A proof-of-concept study

Abstract: Background:Extracranial–intracranial bypass is a challenging procedure that requires special microsurgical skills and an operative microscope. The exoscope is a tool for neurosurgical visualization that provides view on a heads-up display similar to an endoscope, but positioned external to the operating field, like a microscope. The authors carried out a proof-of-concept study evaluating the feasibility and effectiveness of performing microvascular bypass using various new exoscopic tools.Methods:We evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 35 publications
5
15
0
Order By: Relevance
“…Similarly, during tympanoplasty, we found that the microscope was more comfortable when removing the cholesteatoma or granulation tissue from the tympanic cavity and hidden areas of the middle ear (stages T6 and T7). Similar observations in microvascular bypass procedures have been reported [ 14 ]. As those studies have shown, microvascular anastomosis is feasible under 3D exoscope visualization; however, at the highest magnification, the depth perception is inferior to that provided by a standard operating microscope, which impedes the procedure [ 14 ].…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, during tympanoplasty, we found that the microscope was more comfortable when removing the cholesteatoma or granulation tissue from the tympanic cavity and hidden areas of the middle ear (stages T6 and T7). Similar observations in microvascular bypass procedures have been reported [ 14 ]. As those studies have shown, microvascular anastomosis is feasible under 3D exoscope visualization; however, at the highest magnification, the depth perception is inferior to that provided by a standard operating microscope, which impedes the procedure [ 14 ].…”
Section: Discussionsupporting
confidence: 88%
“…The utilization of a hybrid visualization system like the one investigated in this study can help adjust workflows and gain experience in more complex microneurosurgical tasks before switching to a standalone exoscope. Until completion of this paper, one other study on the same system has been published [ 4 ] presenting results of a comparative preclinical assessment of microvascular anastomosis. The authors conclude that the 3D4k exoscope allows for neurovascular task completion; however, in their evaluation, size and width of the field of view as well as sharpness and resolution at high magnification were still superior in ocular mode.…”
Section: Discussionmentioning
confidence: 99%
“…From the clinical perspective, this device evolution is designed to address current constraints in surgical access and ergonomics, digitally enhanced visualization and information sharing in the OR, all of which can have high impact on surgical interventions of varying complexity. Exoscope technology is trying to overcome previously experienced limitations in endoscopy and surgical microscopy [ 25 , 26 ] by merging these two major intraoperative visualization techniques [ 4 , 22 ] and seeking to establish new quality standards [ 4 ]. An exoscope is an extracorporeal scope [ 13 ] distanced from the surgical site, producing high-quality video images with a wide field of view [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that microsurgical performance under two-dimensional visualization is possible but requires more time and may be not so effective, compared with a three-dimensional visualization. 35 , 36 …”
Section: Discussionmentioning
confidence: 99%